Music Therapy and Psychoneuroimmunological Markers in Children With Chronic Disease: A Systematic Review - Hasanah, Idyatul; Lei, Chui Ping; Haikal, Zikrul; Sari, Apriani Susmita; Soares, Domingos; Prihatin, Kurniati (Jurnal Berita Ilmu Keperawatan, 2025)
Stress conditions in children with chronic disease affect psychoneuroimmunological markers. One of the mind-body modalities commonly used in pediatric chronic disease is music therapy. This systematic aim was evaluating the effect of music therapy on psychoneuroimmunological markers among children with chronic disease. Articles published between March 31, 2014, and April 1, 2023, were retrieved from five databases: Scopus, PubMed, Web of Science, EBSCOhost, and ProQuest. Rayyan, an AI-powered tool for systematic literature reviews, facilitated paper selection. Studies were screened based on pre-defined inclusion and exclusion criteria. The PRISMA checklist guided selection, and the JBI Critical Appraisal for quality assessment. Data analysis employed a descriptive approach. A total of 15 articles published between 2014 and 2023 were included in this review. 10 (66,7%) of 15 studies assessed the effectiveness of music therapy on psychological and physiological responses. Meanwhile, five (33,3%) studies assessed the effectiveness of music therapy on neuroimmunological markers. Among the five studies, one did not exhibit a statistically significant impact. In contrast, the remaining four studies displayed a significant impact of music therapy on neuroimmunological markers. The most studies assessed the impact of music therapy on psychological and physiological responses, but only a small proportion assessed the effectiveness of music therapy on neuroimmunological markers. Music therapy can be considered a safe and generally well-accepted intervention in pediatric health care to manage psychoneuroimmunological markers.